Setting up a COVID-19 care facility at a prison: An experience from Pakistan (2020)
Since its emergence from Wuhan at the end of last year, the novel coronavirus has spread to almost every country of the earth posing a significant challenge to healthcare systems everywhere. This article presents a practical model adopted in light of the WHO guidelines which was used by our team to set up the facility and care for the 69 COVID-19 prisoners within the prison itself. In addition to the challenges posed by the COVID-19 the healthcare team also had to overcome the challenge of the unique nature of the setup. The purpose of this article is to describe our response to help providers tasked with caring for prisoners especially in lower socio-economic countries.